1990
DOI: 10.1515/hfsg.1990.44.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Brown-rotted Lignin

Abstract: Naturally brown-rotted lignin was structurally characterized by various chemical and spectroscopic techniques. Our results of extensively decayed Douglas-fir indicate that modification of lignin by brownrot fungi is mainly oxidative. In addition to modification of aromatic ring structures by demethylation, advanced decay by brown-rot fungi proceeds in the direction of partial depolymerization, perhaps involving aryl ether interunit bond cleavage, and oxidation and cleavage of the lignin side chain structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 9 publications
(15 reference statements)
0
35
0
4
Order By: Relevance
“…Highley (1988) found numerous species of brown rots that were able to solubilise microcrystalline cellulose. These fungi simply depolymerise cellulose, without producing Jin et al (1990), Eriksson et al (1990) soluble monomers or dimers. Still, no additional enzyme has been found to account for the lost exoglucanase that splits off from the soluble components.…”
Section: Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Highley (1988) found numerous species of brown rots that were able to solubilise microcrystalline cellulose. These fungi simply depolymerise cellulose, without producing Jin et al (1990), Eriksson et al (1990) soluble monomers or dimers. Still, no additional enzyme has been found to account for the lost exoglucanase that splits off from the soluble components.…”
Section: Cellulosementioning
confidence: 99%
“…The radicals made by brown-rot fungi can eradicate methoxyl groups from lignin and yield methanol, leaving the remains of mostly altered lignin (Eriksson et al 1990) where the presence of phenolic hydroxyl groups is high (Crawford 1981). Carbonyl and carboxyl groups are also produced (Jin et al 1990). Hence brown-rotted lignin remains more responsive than natural lignin.…”
Section: Lignin Degradation By Brown-rot Fungimentioning
confidence: 99%
“…Analysis of 26 samples by solid-state 13 C NMR showed that decomposition generally proceeded first by nonselective mass loss, followed by more rapid loss of carbohydrate C and increasing concentration of lignin C, only slightly altered by oxidation and small increase of alkyl (lipid) C. This pattern is consistent with initial decomposition by white-rot fungi, with non-selective mass loss and little change in overall organic composition, or even depletion of lignin. The second stage, with increasing concentration of lignin and colour change to dark reddish-brown, indicates a dominance of brown-rot fungi that have a very limited ability to decompose lignin (Hedges et al 1988;Jin et al 1990). In this study, we examined relationships among decay class, density, total C, δ 13 C and NMR-determined lignin for a larger set of CWD samples from the CFC plots and some related samples.…”
mentioning
confidence: 99%
“…The comparison to the period of C-01 and WS treatments shows no significant difference. As previously reported BRF do not degrade lignin extensively [38][39][40][41] but chemically modify it 11,42 . With increasing time in the degradation, the chips wood progressively turned dark brown taking on a friable texture and shrinking in volume with time.…”
Section: Wood Biodegradation Processmentioning
confidence: 92%